Chitosan Extraction from Anabas testudineus Scales for Enhancing the Properties of Edible Corn Starch-Based Films: Characterization and Performance Evaluation - Ristianingsih, Yuli; Hernadin, Ivan Aldino; Timotius, Daniel (Makara Journal of Science, 2025)
The papuyu fish (Anabas testudineus) is a freshwater species found in South and Southeast Asia. It is known for its ability to survive in extreme conditions, such as low oxygen levels and poor water quality, making it a potential candi-date for climate-resilient aquaculture. In this study, chitosan was extracted from the scales of papuyu fish through de-mineralization using 1 N HCl solution, deproteination using 5% NaOH solution, and deacetylation using 70% NaOH solution, resulting in an overall yield of 5.11%. The extracted chitosan was added to edible film made from corn starch, and the properties of the prepared films were characterized via Fourier transform infrared spectroscopy, scanning elec-tron microscopy, water solubility test, and water vapor permeability test. Fourier transform infrared spectroscopy re-vealed the presence of characteristic peaks of chitosan, such as amide I (C=O) and amide II (C–N), at around 1647.26 cm−1. Scanning electron microscopy revealed the presence of pores in the edible films. Furthermore, the water solubility of the prepared films decreased with increasing chitosan content. However, the addition of chitosan did not significant-ly affect the permeability